Fostering transformational leadership among administrative staff in higher education: strategies for institutional success / Kamarul Aini Hassan Basri and Farah Adilla Ab Rahman - Hassan Basri, Kamarul Aini; Ab Rahman, Farah Adilla (Universiti Teknologi MARA, Negeri Sembilan, 2024)
In today’s rapidly evolving academic landscape, developing leadership skills among administrative staff is not just a valuable asset but a critical investment for higher education institutions. Leadership plays a key role in addressing both present and future challenges, with transformational leadership emerging as a powerful model for driving necessary changes in educational environments (Lamm et al., 2021). This leadership style inspires and motivates staff members, aligning their individual development with the strategic objectives and administrative needs of the institution. Transformational leadership emphasizes empowering administrative staff, fostering their connection to institutional goals, and promoting a sense of ownership in their roles. In times of rapid change and growing complexity, raising awareness about the importance of leadership processes and comprehensive leadership training programs becomes essential. These programs are vital for fostering innovation, adaptability, and resilience, helping institutions to effectively respond to local, national, and global challenges (Dumulescu & Muțiu, 2021).